ANALISIS PERTUMBUHAN DAN TINGKAT KELANGSUNGAN HIDUP IKAN NILA (Oreochromis niloticus) DENGAN PEMBERIAN PAKAN PELET DARI SUMBER YANG BERBEDA - Elrifadah - Elrifadah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This study was aim to determine the different pellet feed source on the growth and survival rate of Nile tilapia. The purpose of this research was to provide information of the best feed for the growth and survival rate of Nile tilapia.Completely Randomized Design, with 3 treatments ( treatment A: community-made pellet, treatment B: commercial pellet PF500; treatment C: commercial pellet 885) and 3 replicate was used for the research. Nile tilapia with 3-4 cm length placed in nine aquariums with stocking density 6 fishes/L. Feeding treatment given twice a day at level 3 %/ body weight. The parameters observed include growth rates, survival, and feed conversion. Supporting data was observed for water quality. Observation was carried out for 30 days.The results showed that the average weight, in treatment A was 101,66 g, treatment B was 118.33 g, and treatment C was 128.33 g. The average yield of relative growth in treatment A was 111.44%, treatment B was 134.23%, and treatment C was 135.76%. Treatment C shows the highest value, then treatment B and treatment A. The average yield of feed conversion, treatment A was 1.11; treatment B 3.21; and treatment C was 3.37. Survival rate of all treatments was 100%.